Let's Learn Japanese with Hiragana and Katakana. - Kai, Masumi (Cambridge Scholars Publishing, 2013)
This book aims to teach Japanese characters step by step, whilst also simultaneously highlighting vocabulary needed by beginners. Each word comes with an illustration to facilitate the reader's visual learning. The book also contains information on how to write a sentence by using the characters and vocabulary presented to the reader and contains exercises that teachers can use as homework. The attached CD contains the sounds of each character, vocabulary exercises, and instructions on how to ...